Identification of Candidate Genes for a Major Quantitative Disease Resistance Locus From Soybean PI 427105B for Resistance to Phytophthora sojae - Karhoff, Stephanie; Vargas-Garcia, Christian; Lee, Sungwoo; Mian, M. A. Rouf; Graham, Michelle A.; Dorrance, Anne E.; McHale, Leah K. (Frontiers in Plant Science, 2022)
Phytophthora root and stem rot is a yield-limiting soybean disease caused by the soil-borne oomycete Phytophthora sojae. Although multiple quantitative disease resistance loci (QDRL) have been identified, most explain less than 10% of the phenotypic variation (PV). A major QDRL explaining up to 45% of the PV was previously identified on chromosome 18 and represents a valuable source of resistance for soybean breeding programs. Resistance alleles from Plant introductions 427105B and 427106 significantly increase yield in disease-prone fields and result in no significant yield difference in fields with little to no disease pressure. In this study, high resolution mapping reduced the QDRL interval to 3.1 cM, and RNA-seq analysis of near-isogenic lines (NILs) varying at QDRL-18 pinpointed a single gene of interest which was downregulated in inoculated NILs carrying the resistant allele compared to inoculated NILs with the susceptible allele. This gene of interest putatively encodes a serine threonine kinase (STK) related to the AtCR4 family, and may be acting as a susceptibility factor, based on the specific increase of jasmonic acid concentration in inoculated NILs. This work facilitates further functional analyses and marker-assisted breeding efforts by prioritizing candidate genes and narrowing the targeted region for introgression.